Diversidad de comunidades microbianas en suelos y aguas del área de concesión para la conservación cuenca alta río Itaya, Iquitos-Perú 2020 - Estela Moreno, Segundo Levi (2022)
Metagenomic analysis is very valuable because it allows us to obtain the genetic information of the microorganisms present in a sample. The main objective was to determine the diversity of microbial communities in the soils and waters of the Upper Itaya River Basin Conservation Concession Area (CCCARI). The selection criteria for the soil samples were their typology, topography and relief; for the water samples, these were collected from cochas streams and the Itaya River, and the physicochemical parameters of both samples were determined. Metagenomic DNA from soils and water were purified with standard methods, libraries were prepared and then sequenced on the Illumina NextSeq™ 550 platform. The sequences were processed using the MG-RAST server. The results indicate that the soils are of loam and slightly acidic textural class. The water samples exhibited physicochemical characteristics typical of black waters. Additionally, the massive sequencing indicates a high microbial diversity in the soils and waters of the CCCARI with a predominance of bacteria. Taken together, these results indicate that the microbial diversity recorded in the CCCARI soil and water samples is partly attributed to the physicochemical characteristics of these environments.